2020
DOI: 10.1007/s00701-019-04196-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical nuances and placement of subgaleal drains for supratentorial procedures—a prospective analysis of efficacy and outcome in 150 craniotomies

Abstract: Background For supratentorial craniotomy, surgical access, and closure technique, including placement of subgaleal drains, may vary considerably. The influence of surgical nuances on postoperative complications such as cerebrospinal fluid leakage or impaired wound healing overall remains largely unclear. With this study, we are reporting our experiences and the impact of our clinical routines on outcome in a prospectively collected data set. Method We prospectively observed 150 consecutive patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…In a univariate analysis, we found no difference in outcomes between the DG vs NDG (p = 0.624). Our findings were similar to a prospective study by Hamou and colleagues 26 which evaluated the efficacy of subgaleal drains among 150 consecutive patients undergoing supratentorial craniotomy similarly found that presence of drainage posed no influence on the outcome, although their study further reported that curved incisions, bigger craniotomy, and tumor size, were related with higher occurrence of subgaleal fluid collection (p < 0.0001, p = 0.001, p < 0.01 respectively). More supporting findings were reported by Choi and group who noted that utility of post craniotomy drains did not appear to be important for prevention of post craniotomy SFC as well as for promotion of surgical site healing in pterional craniotomy 27 …”
Section: Discussionsupporting
confidence: 90%
“…In a univariate analysis, we found no difference in outcomes between the DG vs NDG (p = 0.624). Our findings were similar to a prospective study by Hamou and colleagues 26 which evaluated the efficacy of subgaleal drains among 150 consecutive patients undergoing supratentorial craniotomy similarly found that presence of drainage posed no influence on the outcome, although their study further reported that curved incisions, bigger craniotomy, and tumor size, were related with higher occurrence of subgaleal fluid collection (p < 0.0001, p = 0.001, p < 0.01 respectively). More supporting findings were reported by Choi and group who noted that utility of post craniotomy drains did not appear to be important for prevention of post craniotomy SFC as well as for promotion of surgical site healing in pterional craniotomy 27 …”
Section: Discussionsupporting
confidence: 90%
“…35 In a prospective study of 150 patients undergoing craniotomy, Hamou and colleagues found no difference in periorbital edema, subgaleal swelling, impaired wound healing, non-adequate pain control, or need for re-operation between patients with and without subgaleal drains. 136 The authors did find that longer, curved incisions and larger craniotomies were associated with a significantly higher rate of subgaleal swelling. Although the underlying mechanism behind the inferior cosmetic outcomes in patients with postoperative drains in our systematic review are unclear, given the small size of the space created with this approach, the lack of data supporting benefit of postoperative drains in cranial neurosurgery, and the association with poor cosmetic outcome in this report, the potential risks of a subgaleal drain placement outweigh the benefits.…”
Section: Discussionmentioning
confidence: 94%
“…Subgaleal drain placement is a widespread practice across many surgical fields, and closed-suction drains are frequently left after cranial neurosurgery despite limited data to support their benefit. Drains are often used after cranial procedures in hopes of evacuating blood and serous fluid, which can interfere with wound healing and serve as a nidus for infection.. 35,136 Despite this, Choi and colleagues conducted a retrospective review of 607 patients who had undergone pterional craniotomy and compared outcomes stratified by postoperative drain placement. 35 The non-drain group had a lower incidence of postoperative epidural hematomas and less postoperative increase in thickness of the myocutaneous flap compared with the drain group.…”
Section: Factors Affecting Patient Cosmesismentioning
confidence: 99%
“…Among several clinical factors, including sex, age, interval, defect size, and material type, PEEK was the only predictor of subgaleal effusion. Of note, individual surgical nuances such as the type of dural closure may affect the rate of subgaleal fluid collection ( 39 ). The dura was carefully protected during our surgery, and a clear inspection of the dura for potential CSF leakage was routinely performed at the end of the surgery.…”
Section: Discussionmentioning
confidence: 99%